2003
DOI: 10.1210/jc.2003-030144
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Growth Hormone on Vascular Function in Human Subjects

Abstract: GH is involved in the long-term regulation of peripheral vascular resistance and vascular reactivity. We determined whether GH plays a role in the acute regulation of vascular function in humans. The acute vascular effects of GH were studied in eight healthy subjects according to a double-blind, placebo-controlled design. Forearm blood flow (FBF), vascular resistance, and nitric oxide (NO) production were monitored during a 4-h infusion of GH into the brachial artery at a rate chosen to raise local GH to stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 17 publications
2
37
2
1
Order By: Relevance
“…In contrast to the findings described above, both in vitro [26] and in vivo studies [27,28] indicate that GH induces eNOSmediated NO production. In the human endothelial cell line, EAht926, high concentrations of GH regulate eNOS expression and NO production [26] , effects that also occur in human aortic endothelial cells [29] .…”
Section: Introductioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In contrast to the findings described above, both in vitro [26] and in vivo studies [27,28] indicate that GH induces eNOSmediated NO production. In the human endothelial cell line, EAht926, high concentrations of GH regulate eNOS expression and NO production [26] , effects that also occur in human aortic endothelial cells [29] .…”
Section: Introductioncontrasting
confidence: 71%
“…Clinical studies indicate that GH is one of many factors regulating vascular homeostasis [1,53] ; Napoli et al [28] demonstrated that the exogenous administration of GH induced local vasodilation in a rat model, an effect that was related to increased of NO levels and promoted endothelial sensitivity to vasorelaxants, such as ACh; however, they did not www.nature.com/aps Gonzalez C et al Acta Pharmacologica Sinica npg clarify which signaling molecules were involved but hypothesized that the local action of the hormone was responsible for the observed effects. We demonstrated that GH and PL act directly on the GHR in endothelial cells, promoting both vasodilation and NO release.…”
Section: Discussionmentioning
confidence: 99%
“…Indices of NO formation are low in patients with GH deficiency whereas replacement therapy with GH results in increased rates of NO synthesis [14]. GH given in vivo and in vitro stimulates eNOS gene and protein expression, as well as NO release from the endothelium [15,16]. On a molecular level, preliminary studies have suggested that the Akt pathway is involved in GH-mediated induction of eNOS activity.…”
Section: Introductionmentioning
confidence: 99%
“…(A) The number of early-outgrowth EPCs increased following growth hormone administration (13 CFU per HPF[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] to 19), (B) whereas the number of late-outgrowth EPCs did not significantly change (4 CFU per HPF[2][3][4][5][6][7][8][9][10][11] to 1 [0-4]). Data presented as median with interquartile range (N = 10).…”
mentioning
confidence: 99%
“…The growth hormone also conditions the proper composition of the body, mostly within the volume and topography of the fat tissue, as well as it regulates the proper development and functioning of many organs and organ systems, like heart and circulatory system, brain and nervous system, stomach and digestive system, kidneys and excretory system, as well as lungs and respiratory tract (Nass et al, 1995;Merola et al, 1996;Parks et al, 1998;Waters et al, 1999;Frago et al, 2002;Napoli et al, 2003;Dattani, Preece, 2004;Biller, 2007;Krysiak, Okopień, 2007;Harvey, 2010).…”
Section: Hormone Of Growth Only?mentioning
confidence: 99%